Culture and dignity in Latin America. Discoloniality of social inequality - Mejía Navarrete, Julio Víctor (2017)
The article analyzes some initial questions on the development of the cultural conflict that defines the pace of the contemporary life of Latin America. It emerges a new subjectivity which denies the dominant forms of thinking society in terms of the differences and emerge an episteme in function of social equality.